The influence of knowledge and accessibility on customer saving decisions with religiosity as a moderation variable - Basri, Muh. Arfah; Wahab, Abdul; Awaluddin, Murtiadi; Muchlis, Mustakim; Kouach Yassine (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2024)
This study aims to determine the influence of knowledge and accessibility on customer saving decisions at Bank Syariah Indonesia with religiosity as a moderation variable. This type of research is quantitative research. The population in this study is all students of the Department of Sharia Economic Law STAI YAPIS Takalar. The sampling techniques used are: purposive sampling. In this study the sample number was 41 people. The data collection technique used is a questionnaire measured by a Scale Likert. Data analysis techniques Moderating Regression Analysis (MRA) with the help of the program SPSS 24.0 for windows. The results showed that 1) simultaneously knowledge and accessibility have a significant effect on customers' saving decisions at Bank Syariah Indonesia, 2) knowledge has a significant effect on customers' saving decisions at Bank Syariah Indonesia, 3) accessibility has a significant effect on customers' saving decisions at Bank Syariah Indonesia, 4) religiosity is unable to moderate the influence of knowledge on customers' saving decisions at Bank Syariah Indonesia, 5) religiosity is able to moderate accessibility to customers' saving decisions at Bank Syariah Indonesia.